A bibliometric analysis of graphene in acetaminophen detection: Current status, development, and future directions. (November 2022) - Xiang, Shuyan; Mao, Shuduan; Chen, Fei; Zhao, Shichao; Su, Weitao; Fu, Li; Zare, Najmeh; Karimi, Fatemeh
Abstract: Acetaminophen is a widely used analgesic throughout the world. Detection of acetaminophen has particular value in pharmacy and clinics. Electrochemical sensors assembled with advanced materials are an effective method for the rapid detection of acetaminophen. Graphene-based carbon nanomaterials have been extensively investigated for potential analytical applications in the last decade. In this article, we selected papers containing both graphene and acetaminophen. Bibliometrics was used to analyze the relationships and trends among these papers. The results show that the topic has grown at a high rate since 2009. Among them, the detection of acetaminophen by an electrochemical sensor based on graphene is the most important direction. Graphene has moved from being a primary sensing material to a substrate for immobilization of other active ingredients. In addition, the degradation of acetaminophen using graphene-modified electrodes is also an important direction. We analyzed the research history and current status of this topic through bibliometrics. Authors, institutions, countries, and key literature were discussed. We also proposed perspectives for this topic. Graphical abstract: Image 1 Highlights: Bibliometrics was used to analyze the relationships and trends graphene in acetaminophen detection. Authors, institutions, countries, and key literatures were discussed. The application of graphene in soil remediation was discussed. Current status, development, and future directions of graphene for acetaminophen detection were discussed.